Performance characteristics and digestion of growing rabbits fed Corn Gluten Residue Meal (CGRM), Soybean Gluten Residue Meal (SGRM), and Sorghum Brewer Dry Grain (SBDG) - SK Ayandiran; I Adekunle (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2023)
Context: Grain by-products are nonconventional feed resources that can be used as supplemental diets for rabbits, especially during the dry season when native forages are scarce and limiting in essential nutrients. Hence, this present study is to determine the inclusion of residue, Corn Gluten Residue Meal (CGRM), Soybean Gluten Residue Meal (SGRM), and Sorghum Brewer Dry Grain (SBDG) as a replacement for maize on the performance and digestion coefficient of growing rabbits. Methods: Forty mixed breeds of rabbits (4 - 6 weeks old) were allotted into four experimental treatments in a completely randomized design. Four experimental diets were then compounded by replacing maize (40% inclusion level) with CGRM, SGRM, and SBDG then fed to the growing rabbits at 3% of their body weight.  Results: The crude protein contents of diets containing grain by-products (19.06% - 20.87%) were better than maize (12.96%). Evidently, the maize diet (55.56%) was higher in carbohydrate fraction than these grain by-product-containing diets (42.20 - 49.98). Rabbits fed diets containing grain by-products had significantly higher (p < 0.05) feed intake and final weight compared to rabbits fed maize. Rabbits-fed diets containing CGRM (87.41%) and SGRM (92.09%) were significantly higher (p < 0.05) in digestible crude protein than maize (76.79%) and SBDG (74.29%) diets. Also, diets containing maize and SGRM were significantly higher (p < 0.05) in the digestible carbohydrate fraction than diets. Whereas, rabbits fed diets CGRM and SBDG had significantly better (p < 0.05) nitrogen balance and retention compared to rabbits fed diet SGRM and maize.  Conclusion: It could be concluded that the inclusion of CGRM, SGRM, and SBDG led to better performances and digestion but with inferior carbohydrate fractions and digestion percentages compared to the maize diet.